Water diffusion to assess meat microstructure. (1st December 2017) - Laghi, Luca; Venturi, Luca; Dellarosa, Nicolò; Petracci, Massimiliano
Highlights: In meat water exchanges between spaces inside and outside myofibrils. TD-NMR can evaluate water diffusion in meat inside and outside myofibrils. Freezing causes modifications to meat microstructure evaluated by water diffusion. Abstract: In the quest for setting up rapid methods to evaluate water retention ability of meat microstructures, time domain nuclear magnetic resonance (TD-NMR) has gained a prominent role, due to the possibility to observe water located outside the myofibrils, easily lost upon storage or cooking. Diffusion weighted signals could be used to monitor the shape and dimension of the pores in which water is confined, thus boosting the information offered by TD-NMR. The work outlines a parsimonious model to describe relative abundance and diffusion coefficient of intra and extra myofibrillar water populations, exchange rate between them, diameter of the myofibrillar cells. To test our model, we registered diffusion and T2 weighted NMR signals at 20 MHz on fresh meat from pectoralis major muscle of 100 days old female turkey. We then purposely altered water distribution and myofibrils shape by means of freezing. The model predicted nicely the consequences of the imposed modifications.